Quality of Life Changes After Chronic Total Occlusion Angioplasty in Patients With Baseline Refractory Angina. (March 2019) - Hirai, Taishi; Grantham, J. Aaron; Sapontis, James; Cohen, David J.; Marso, Steven P.; Lombardi, William; Karmpaliotis, Dimitri; Moses, Jeffrey; Nicholson, William J.; Pershad, Ashish; Wyman, R. Michael; Spaedy, Anthony; et al.
Abstract : Background: Health status and quality of life improvement after chronic total occlusion (CTO) percutaneous coronary intervention (PCI) among patients with refractory angina has not been reported. We sought to determine the degree of quality of life improvement after CTO PCI in patients with refractory angina. Methods and Results: Among 1000 consecutive patients who underwent CTO PCI in a 12-center registry, refractory angina was defined as any angina (baseline Seattle Angina Questionnaire [SAQ] Angina Frequency score of ⩽90) despite treatment with ≥3 antianginal medications. Health status at baseline and 1-year follow-up was quantified using the SAQ. Refractory angina was present at baseline in 148 patients (14.8%). Technical success was achieved in 120 (81.1%) at the initial attempt and major adverse cardiac and cerebral events occurred in 10 (6.8%). There were no procedural deaths. Refractory angina patients were highly symptomatic at baseline with mean SAQ Angina Frequency of 51.1±23.8, SAQ quality of life of 35.3±21.2, and SAQ Summary Score of 47.2±17.9, improving by 32.0±27.8, 35.7±23.9, and 32.1±20.1 at 1 year. Through 1-year follow-up, patients with successful CTO PCI had significantly larger degree of improvement of SAQ Angina Frequency and SAQ Summary Score (35.0±26.8 versus 18.8±28.9, P <0.01; 34.2±19.4 versus 22.5±20.8, P <0.01) compared with unsuccessful CTO PCI. Conclusions: Refractory angina was present in 1 of 7 patients in the OPEN-CTO (Outcomes, Patient Health Status, and Efficiency in Chronic Total Occlusion Hybrid Procedures) registry. Patients with refractory angina experienced large, clinically significant health status improvements that persisted through 12 months, and patients with successful CTO PCI had larger health status improvement than those without. Abstract : Supplemental Digital Content is available in the text.